2018
DOI: 10.1002/eat.22871
|View full text |Cite
|
Sign up to set email alerts
|

Core psychopathology in anorexia nervosa and bulimia nervosa: A network analysis

Abstract: Findings support the cognitive-behavioral premise that shape and weight overvaluation are at the core of AN psychopathology. Our BN and combined network findings provide a high degree of replication of previous findings. Clinically, findings highlight the importance of considering shape and weight overvaluation as a severity specifier and primary treatment target for people with EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
126
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(162 citation statements)
references
References 41 publications
29
126
5
2
Order By: Relevance
“…(Dietary) restraint was the only behavioral symptom that was highly central in the ED cluster with strong connections to other behavioral symptoms, namely, restrictive eating and following dieting rules. This corroborates previous research that showed high centrality for restraint in AN and BN networks (Forrest et al, ). With regard to these findings, ED treatment should focus on re‐establishing regular eating patterns by for example, providing meal plans.…”
Section: Discussionsupporting
confidence: 93%
“…(Dietary) restraint was the only behavioral symptom that was highly central in the ED cluster with strong connections to other behavioral symptoms, namely, restrictive eating and following dieting rules. This corroborates previous research that showed high centrality for restraint in AN and BN networks (Forrest et al, ). With regard to these findings, ED treatment should focus on re‐establishing regular eating patterns by for example, providing meal plans.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, shape overvaluation and desiring weight loss were among the most central symptoms in the current study, and either or both of these symptoms have emerged as central in several other studies (Forrest et al, 2018;Levinson, Zerwas, et al, 2017;Wang et al, in press). For instance, shape overvaluation and desiring weight loss were among the most central symptoms in the current study, and either or both of these symptoms have emerged as central in several other studies (Forrest et al, 2018;Levinson, Zerwas, et al, 2017;Wang et al, in press).…”
Section: Similarities and Differences With Past Studiessupporting
confidence: 63%
“…The premise that some ED symptoms play a more fundamental role in maintenance and treatment aligns well with network theory, which holds that symptom interactions are what cause psychopathology (Borsboom & Cramer, 2013). In the ED field, multiple studies have identified central ED symptoms, such as desiring weight loss, shape and weight overvaluation, weight dissatisfaction, body checking, and dietary restraint (DuBois, Rogers, Franko, Eddy, & Thomas, 2017;Forbush, Siew, & Vitevitch, 2016;Forrest, Jones, Ortiz, & Smith, 2018;Goldschmidt et al, 2018;Wang, Jones, Dreier, Elliott, & Grilo, in press). In the ED field, multiple studies have identified central ED symptoms, such as desiring weight loss, shape and weight overvaluation, weight dissatisfaction, body checking, and dietary restraint (DuBois, Rogers, Franko, Eddy, & Thomas, 2017;Forbush, Siew, & Vitevitch, 2016;Forrest, Jones, Ortiz, & Smith, 2018;Goldschmidt et al, 2018;Wang, Jones, Dreier, Elliott, & Grilo, in press).…”
Section: Intoductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Existing research on network analyses in EDs supports the Transdiagnostic Model (DuBois, Rodgers, Franko, Eddy, & Thomas, ). In multiple studies of individuals with EDs, items related to overvaluation of weight, shape, and the strict control of weight and shape emerged among the most central nodes of the network (DuBois et al, ; Forbush, Siew, & Vitevitch, ; Forrest, Jones, Ortiz, & Smith, Goldschmidt et al, ; Wang, Jones, Dreier, Elliott, & Grilo, ). Past research also suggests that dietary restraint plays an important role in the maintenance of eating pathology (DuBois et al, ; Forrest et al, ).…”
Section: Network Analysismentioning
confidence: 99%